Endplate volumetric bone mineral density biomechanically matched interbody cage - Weng, Yuanzhi; Di, Mingyuan; Wu, Tianchi; Ma, Xinlong; Yang, Qiang; Lu, Weijia William (Frontiers in Bioengineering and Biotechnology, 2022)
Disc degenerative problems affect the aging population, globally, and interbody fusion is a crucial surgical treatment. The interbody cage is the critical implant in interbody fusion surgery; however, its subsidence risk becomes a remarkable clinical complication. Cage subsidence is caused due to a mismatch of material properties between the bone and implant, specifically, the higher elastic modulus of the cage relative to that of the spinal segments, inducing subsidence. Our recent observation has demonstrated that endplate volumetric bone mineral density (EP-vBMD) measured through the greatest cortex-occupied 1.25-mm height region of interest, using automatic phantomless quantitative computed tomography scanning, could be an independent cage subsidence predictor and a tool for cage selection instruction. Porous design on the metallic cage is a trend in interbody fusion devices as it provides a solution to the subsidence problem. Moreover, the superior osseointegration effect of the metallic cage, like the titanium alloy cage, is retained. Patient-specific customization of porous metallic cages based on the greatest subsidence-related EP-vBMD may be a good modification for the cage design as it can achieve biomechanical matching with the contacting bone tissue. We proposed a novel perspective on porous metallic cages by customizing the elastic modulus of porous metallic cages by modifying its porosity according to endplate elastic modulus calculated from EP-vBMD. A three-grade porosity customization strategy was introduced, and direct porosity-modulus customization was also available depending on the patient’s or doctor’s discretion.